(untitled) (NAU Journal of Library and Information Science, 2019)
Social media platforms enable people to access and share information. People also get answers to questions, learn, discover and connect with people, services, clientele and brands on social media. Libraries use social media to provide information services to their users. Social media also play crucial role in distance learning. However, prevalent unethical practices on the platforms by users and the operators themselves have raised serious concerns and ignited discourses of how to regulate the social media. Governments of different countries including Nigeria are mulling over regulations that would control the content and the privacy of users on these platforms. Regulations by government over media have critical implications for access to information and censorship. Operators of social media platforms can self-regulate through setting standards of suitable rules of behaviour and content by and for the operators of social media platforms that are necessary to support freedom of expression and right to access of information and that stipulate how those behaviour will be monitored and enforced. Libraries are irrevocably committed to the right to access information and would advocate that a balance be struck between outright legislation that ‘muzzles’ social media and ensuring that the sustenance of freedom to access to information is guaranteed. Beyond self-regulation by owners of social media platforms, librarians can also teach the public how to self-regulate themselves as they access and share information on social media. Learning to discern fake news and staying safe in online spaces including the social media are embedded in information and media literacy propagated by libraries. It is recommended that librarians from different types of libraries collaborate on how to use the social media platforms as avenues to teach wider society on how to self-regulate their use of the social media.